2019
DOI: 10.1002/joc.5985
|View full text |Cite
|
Sign up to set email alerts
|

Regional scale analysis of trends in rainfall using nonparametric methods and wavelet transforms over a semi‐arid region in India

Abstract: Space‐time variability of rainfall at local scale is affected by several regional factors such as aerosol concentration, greenhouse gases, land cover changes, etc., along with large scale atmospheric circulations. Predictive ability of regional circulation models can be significantly improved and efficient management of water resources can be assured by identifying dominant variables controlling spatiotemporal variations in rainfall among aforementioned factors. The present study aims to investigate dominant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…The intrinsic nature of drought has made understanding, monitoring and evaluating adaptation to drought hazards difficult. In addition, identifying the onset of drought conditions is more difficult than with other natural hazards, as it usually occurs due to many factors which become apparent only after a prolonged period of little or no precipitation [9,10]. The difficulties are also experienced while determining the drought onset, extent and fate [11].…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic nature of drought has made understanding, monitoring and evaluating adaptation to drought hazards difficult. In addition, identifying the onset of drought conditions is more difficult than with other natural hazards, as it usually occurs due to many factors which become apparent only after a prolonged period of little or no precipitation [9,10]. The difficulties are also experienced while determining the drought onset, extent and fate [11].…”
Section: Introductionmentioning
confidence: 99%
“…In various places in India, it was found that the annual and monsoon time series having similar results in trend analysis even the level of significance is also matched (Patra et al 2012;Chandniha et al 2016;Pal et al 2019). The insignificantly decreasing trends in pre-monsoon and post-monsoon rainfall are found in the majority of districts of Odisha during 1901-2013.…”
Section: Discussionmentioning
confidence: 68%
“…Many researchers and authors suggested similar combinations as presented in Table 2 [7,52,80,83,[88][89][90]. These proposed models may not have a central role to play in the decision-making process regarding trend component existence [14,81].…”
Section: Combining Triangular Trend Analysis Methodology With Discret...mentioning
confidence: 98%